ANALISIS IMPLEMENTASI PENGAJARAN MIKRO DALAM PROGRAM STUDI PENDIDIKAN JASMANI: TANTANGAN DAN SOLUSI - Dewi Endriani; Rafika Ardilla; Idam Syafitri Gea; Juner Duompiba Sinaga; A.Martua Pangidoan; Gollen Naibaho; Gabriel B Sinaga; Edwaard R Pakpahan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of microteaching in the physical education study program and identify various challenges faced by students and possible solutions. Microteaching is a crucial course in preparing prospective teachers to develop effective teaching skills. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of microteaching has been successful, but several challenges remain, such as limited mastery of the material, lack of student confidence, and minimal use of learning media. Possible solutions include increasing repeated practice, providing constructive feedback, and utilizing technology in learning. Therefore, optimizing the implementation of microteaching can improve the pedagogical competence of prospective physical education teachers.